Experimental Comparison of Passive Heating/Cooling Space in Lightweight Buildings with Potential Application in Mining Camps. Issue 1 (May 2020) - Villalobos, I; De Gracia, A; Chafer, M; Cabeza, L F; Ushak, S
Abstract: The total energy consumption in a house in Chile includes 30% of heating expenses, increasing to 60% in the winter period. The current energy source are fossil fuels, which can be replaced by the sun, with an efficient implementation of the use of PCM for passive cooling/heating space from solar radiation, benefiting the environment. In the north of Chile there is a solar radiation index of approximately 2750 kWh·m −2, low cloudiness and low precipitation rates, indicating an important source of energy and great opportunity for improvement in the use and management of energy resources. Moreover, mining camps present in large numbers in the northern zone require a lot of energy to cool and heat the space. This research shows the thermal behavior in summer and winter of two lightweight constructions, similar to the type used in mining camps, with dimensions of 2.5 × 2.5 × 2.5 m at pilot scale installed at the University of Antofagasta, Chile. One of these modules contains PCM on the inside of the walls and ceiling, while the other does not, to analyze the effect of PCM by comparison. The results of this work show that in winter (August) the application of PCM favors the permanence within the thermal comfort zone, with a difference of 5°C. In summer there is an opposite effect (January), experiencing a higher temperature increase inside the container with PCM, with a difference of 4°C. According to the constructive characteristics, properties and quantity of PCM used, and the effect of solar radiation on the structure and environmental conditions, there are benefits in energy saving and efficiency in the winter period, while summer shows results that enhance the study and analysis of the applied technology to solve the thermal behavior shown in this season.